KAJIAN DISTRIBUSI KONSENTRASI FOSFAT PADA SEDIMEN SUNGAI BRANTAS HULU DENGAN MENGGUNAKAN TEKNIK DGT (Diffusive Gradient in Thin Film) - Frida Kunti Setiowati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract- The role of phosphate compounds as limiting nutrients for algae growth in aquatic systems contribute to the occurrence of eutrophication in water bodies. Determination of phosphate was performed by in situ sampling methods technique called DGT (Diffusive Gradient in Thin Films). Prob DGT consists of 3 layers as binding gel, diffusive gel, and membrane filters. With the DGT method, phosphate from sediment pore water will through the diffusive gel and accumulate on the binding layer containing La(OH)3. Samples of sediments taking using sediment cores. Samples taken on 2 (two) locations each 3 points of sampling. Measurement of pH, temperature, and conductivity of water sampling conducted at the site.  Profile presence of phosphate is also linked to the presence of nitrate, manganese and iron in the sediments. Analysis of phosphate, nitrate, manganese and iron made by spectrophotometric method. As a results, at location I, the range of phosphate concentration at point A, B and C are consecutive from 0.0630 to 0.1598 ppm, 0.1306 to 0.2185 ppm and 0.1568 to 0.2082 ppm. Phosphate concentration was increased with increasing depth of sediment, while at location II, the phosphate concentration range at point A, B and C are consecutive 0.1204 to 0.2470 ppm, 0.1479 to 0.3466 ppm and 0.1806 to 0.2603 ppm. From this research we canconclude that the sediments of Brantas River downstream has an important role in the phosphate cycle in which these sediments act as a sink and source of phosphate in the waters. Keywords : DGT technique, sediment, phosphate